HADIS LARANGAN MENCEMARI AIR DAN BATAS SELF-PURIFICATION EKOSISTEM: ANALISIS FIKIH AL-BI’AH - Muhammad Alaika Rahim; Ahmad Najib (CV. Denasya Smart Publisher, 2026)
Water pollution and inadequate sanitation remain environmental and public health problems that affect people’s quality of life. In Islam, the Prophet’s hadith contains prohibitions against polluting water, reflecting the importance of cleanliness and public welfare. This study examines the validity of the hadith concerning the prohibition of polluting water, the ‘illat al-hukm underlying it, and its relevance from the perspective of fiqh al-bi’ah to sanitation and water pollution issues. This study aims to analyze the validity of the hadith, identify the ‘illat al-hukm of the prohibition against polluting water, and explain its relevance to the concept of water ecosystem self-purification in modern sanitation. This research employs a library research method with a qualitative-descriptive approach through hadith analysis, fiqh al-bi’ah, and environmental sanitation literature review. The findings show that the hadith prohibiting water pollution is valid and contains principles of preventing public harm, protecting health, and preserving public welfare. The prohibition is not limited to ritual purity but also has ecological relevance to the natural recovery limits of water against pollution. This study concludes that the hadith on prohibiting water pollution has normative and practical relevance as an ethical foundation for addressing contemporary sanitation and water pollution issues.